TRADITIONAL ETHICS AND THE MAINTENANCE OF SOCIAL ORDER IN THE NIGERIAN SOCIETY - Ekeopara, Chike Augustine; Ogbonnaya, Lucky Uchenna (European Scientific Journal, ESJ, 2014)
The concern of this paper is that traditional ethics is the ethics that can lead to peace and unity in Nigeria. The paper argues that this ethics is born out of African ontology which is community-oriented and looks beyond the individual to the community. It posits that this ethics is not distinct from morality and religion: it is an ethics that is lived as well as professed. This ethics holds that immorality brings immediate punishment meted not only on the individual but the entire community. Hence, it is an ethics of fear-fear of the anger of the spiritual world and beings. It also holds that immorality brings shame to the individual as well as those that he/she is connected to. Therefore, the paper asserts that if this ethics is revitalized in the Nigerian society, it will be a morally upright society as well as a socially ordered society with peace and tranquility.